Analysis the Impact of Good Coorporate Governance Towards Profitability of Manufacturing Companies Listed on Indonesia Stock Exchange - Yandi Suprapto (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
The purpose of this study is to determine the impact of good corporate governance toward profitability of Indonesia’s manufacturing companies. This research uses sample of financial report from 107 manufacturing companies listed in Indonesia Stock Exchange in period 2011 to 2015. This research method is purposive sampling by using SPSS program version 22. The result of this research shows that variable independent board independence has a significant negative impact to net profit margin. While other variable independent such as board size, board meeting, and institutional ownership has no significant positive impact to net profit margin. Managerial ownership and audit committee size has no significant negative impact to net profit margin.